Chiral ferrocene-based P, S ligands for Ir-catalyzed hydrogenation of minimally functionalized olefins. Scope and limitations. Issue 21 (26th May 2016) - Biosca, Maria; Coll, Mercè; Lagarde, Florian; Brémond, Emma; Routaboul, Lucie; Manoury, Eric; Pàmies, Oscar; Poli, Rinaldo; Diéguez, Montserrat
Abstract: A family of 12 modular ferrocenyl planar chiral phosphine-thioethers (P, S) has been studied in the asymmetric hydrogenation of minimally functionalized alkenes. These ligands differ by the substituent on sulfur or by the linker between the ferrocene moiety and the sulfur atom (no linker, methylene or methyl substituted methylene linker bearing an additional element of chirality). The cationic iridium(cod) complexes of the different P, S ligands have been efficiently synthesized. For the majority of the ligands, coordination yielded only a single diastereoisomer with full control of the absolute configuration on sulfur. The different iridium complexes have been used in the hydrogenation of various di, tri, and tetrasubstituted minimally functionalized olefins. Conversions and enantioselectivities are highly dependent on the ligand and substrate structure. Full conversions and low-to-excellent enantioselectivities could be obtained (maximum ee from 14 to 94% for 1, 1-disubsituted alkenes, from 17 to 99% for trisubstituted olefins, and 34% for the tetrasubstituted alkene). Graphical abstract: